The influence of time on the magnetic properties of late Quaternary periglacial and alluvial surface and buried soils along the Delaware River, USA - Stinchcomb, Gary E.; Peppe, Daniel J. (Frontiers in Earth Science, 2014)
Magnetic susceptibility of soils has been used as a proxy for rainfall, but other factors can contribute to magnetic enhancement in soils. Here we explore influence of century- to millennial-scale duration of soil formation on periglacial and alluvial soil magnetic properties by assessing three terraces with surface and buried soils ranging in exposure ages from <0.01 to ~16 kyrs along the Delaware River in northeastern USA. The A and B soil horizons have higher Xlf, Ms, and S-ratios compared to parent material, and these values increase in a non-linear fashion with increasing duration of soil formation. Magnetic remanence measurements show a mixed low- and high-coercivity mineral assemblage likely consisting of goethite, hematite and maghemite that contributes to the magnetic enhancement of the soil. Room-temperature and low-temperature field-cooled and zero field-cooled remanence curves confirm the presence of goethite and magnetite and show an increase in magnetization with increasing soil age. These data suggest that as the Delaware alluvial soils weather, the concentration of secondary ferrimagnetic minerals increase in the A and B soil horizons. We then compared the time-dependent Xlf from several age-constrained buried alluvial soils with known climate data for the region during the Quaternary. Contradictory to most studies that suggest a link between increases in magnetic susceptibility and high moisture, increased magnetic enhancement of Delaware alluvial soils coincides with dry climate intervals. Early Holocene enhanced soil Xlf (9.5 – 8.5 ka) corresponds with a well-documented cool-dry climate episode. This relationship is probably related to less frequent flooding during dry intervals allowing more time for low-coercive pedogenic magnetic minerals to form and accumulate, which resulted in increased Xlf. Middle Holocene enhanced Xlf (6.1 – 4.3 ka) corresponds with a transitional wet/dry phase and a previously documented incision event.......